A construção social de um conflito ambiental: a luta do Comitê de Defesa da Ilha contra a implantação da Alcoa - ARAUJO, Raimundo Nonato Gomes (2018)
This dissertation aims to understand the construction of the environmental problem woven by the Defense Committee of the Island. From this boiling process will be examined how thematic and environmental movements emerged in these events. Next, we analyze the process of constitution of the environmental movements in Brazil. It addresses the whole context of Redemocratization that marks the emergence of a more politicized environmentalism in the country. In this process movements emerged with force again in the national scenario, including environmental problems were being woven. There is also a series of contestations in the Maranhão scenario. It is within this context that the formation of the Island Defense Committee takes place, which has built actions and engagements focused on an environmentalist reference against Alcoa's insertion in this region.